2011
DOI: 10.1098/rsif.2011.0679
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity affects self-organization of the soil–microbe system with consequences for function

Abstract: Soils are complex ecosystems and the pore-scale physical structure regulates key processes that support terrestrial life. These include maintaining an appropriate mixture of air and water in soil, nutrient cycling and carbon sequestration. There is evidence that this structure is not random, although the organizing mechanism is not known. Using X-ray microtomography and controlled microcosms, we provide evidence that organization of pore-scale structure arises spontaneously out of the interaction between micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 29 publications
2
112
1
2
Order By: Relevance
“…It is suggested that fungi are crucial to the development of soil pore structure and the selforganization of microbial communities in soils (Crawford et al, 2012) and in soil C dynamics (Bailey et al, 2002). However, given our constraints on the DNA yield from the aggregate groups, and the knowledge that fungi are not uniquely associated with the enzyme assayed herein, b-glucosidase, we pyrosequenced only 16S rRNA genes, which does not capture fungal sequences.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that fungi are crucial to the development of soil pore structure and the selforganization of microbial communities in soils (Crawford et al, 2012) and in soil C dynamics (Bailey et al, 2002). However, given our constraints on the DNA yield from the aggregate groups, and the knowledge that fungi are not uniquely associated with the enzyme assayed herein, b-glucosidase, we pyrosequenced only 16S rRNA genes, which does not capture fungal sequences.…”
Section: Discussionmentioning
confidence: 99%
“…competitors, trophic interactions) and abiotic factors (e.g. soil pH, water content, temperature) in time and space (Naeem and Wright, 2003;Courty et al, 2010;Miller and Fitzsimmons, 2011;Crowther et al, 2012;Crowther and Bradford, 2013). Hence, the expression of fungal traits and their ability to affect soil aggregation has to be evaluated under a variety of conditions, e.g.…”
Section: A Trait-based Approach For Saprobic Fungi In Soil Aggregatiomentioning
confidence: 99%
“…Ecological factors expected to promote diversity [3,4] include spatial structure per se [5] and variable abiotic [4,6,7] and biotic [4,8] environmental features, but the actual contributions of these factors to natural microbial diversity often remain obscure. Among biotic factors, cooperative and competitive social interactions can each affect levels of intra-specific diversity, as can both resource and interference competition [4,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%